Pengaruh Kemampuan Auditor Dalam Mendeteksi Fraud: Kompetensi, Profesionalisme dan Pengalaman Audit - Nasiatul Hana Fikriyah; Cris Kuntadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article aims to determine the influence of competence, professionalism and audit experience in detecting fraud. This article was carried out by conducting a literature study from various research that has been carried out. This article reviews the factors that influence an auditor's ability to detect fraud, namely competence, professionalism and audit experience. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) competency influences the auditor's ability to detect fraud. 2) professionalism influences the auditor's ability to detect fraud and 3) audit experience influences the auditor's ability to detect fraud.